Analisis Pendapatan Usahatani Cabai Keriting Di Kecamatan Kauditan Kabupaten Minahasa Utara - Pariakhan, Oschard; Pangemanan, Lyndon Reinhard J.; Kumaat, Ribka Magdalena (Sam Ratulangi University, 2023)
This study aims to analyze the income of curly chili farming in Kauditan sub-district, North Minahasa regency. This research was conducted in Kauditan District, North Minahasa Regency. This research began from March to June 2022. The method used in this study was purposive with the consideration that Kauditan District is one of the curly chili producing districts. The type of data used in this research is primary and secondary data. The primary data consisted of data on fixed costs, variable costs, investment costs, curly chili production data, curly chili price data, sales data and curly chili cultivation information obtained from field visits and direct interviews with curly chili farmers in Kauditan District. Secondary data in the form of curly chili production development data, curly chili productivity data, and curly chili farming analysis data from other studies obtained from literature studies both obtained in libraries, websites, and other places in the form of the results of previous research related to research problems. The results showed that the income of curly chili farming in Kauditan District, North Minahasa Regency per hectare in one planting cycle with a total of 10,000 plants amounted to IDR225,190,000.